Evaluation of the addition of bupivacaine to intrathecal morphine for intraoperative and postoperative pain management in open liver resections. Issue 2 (February 2022) - Abdel-Kader, Amir K.; Romano, Diana N.; Foote, John; Lin, Hung-Mo; Glasgow, Andrew M.
Abstract: Background: Intrathecal morphine is a popular and effective regional technique for pain control after open liver resection, but its delayed analgesic onset makes it less useful for the intraoperative period. The aim of this retrospective study was to compare the analgesic efficacy and other secondary benefits of the addition of hyperbaric bupivacaine to intrathecal morphine ± fentanyl. We hypothesized that bupivacaine could serve as an analgesic "bridge" prior to the onset of intrathecal morphine/fentanyl thereby lowering opioid consumption and enhancing recovery. Methods: Cumulative intraoperative and postoperative opioid consumption as well as other intra- and postoperative variables were collected and compared between groups receiving intrathecal morphine alone or intrathecal morphine ± hyperbaric bupivacaine. Results: Sixty-eight patients were selected for inclusion. Cumulative intraoperative morphine consumption was significantly reduced in the bupivacaine group while other intraoperative parameters such as intravenous fluids, blood loss, and vasopressors did not differ. There was a statistically significant improvement in time to first bowel movement in the experimental group. Discussion: The intraoperative opioid sparing effects and improved time to bowel function with the addition of hyperbaric bupivacaine to intrathecal morphine may make this technique an easy and low risk method of enhancing recovery after open liver resection.